Space Oppositions as Representatives of SF “Creativity” in M. Tsvetaeva’s Idiolect (Proceedings of Southern Federal University. Philology, 2017)
Irina A. Litvinova (Southern Federal University. Rostov-on-Don, Russian Federation)The article analyzes the semantic field «creativity», which is one of the central in the idiolect of M. Tsvetaeva. The peculiarity of this SF in the author’s texts is its implementation through the author’s modeling of space on the basis of binary oppositions. The material for analysis was prosaic texts, in which this feature of the author’s works is most clearly realized («Natalia Goncharova», «Hero of Labor», «Living On the Living», «From Notebooks and Copybooks»).This M. Tsvetaeva’s feature is conditioned, on the one hand, by the fact that space is one of the central categories in the world picture of M. Tsvetaeva, and often the cognition and representation of even abstract concepts is realized through spatial oppositions. On the other hand, many spatial binary oppositions within the SF «creativity» are realizations of the opposition empty – full, because when characterizing the creator for M. Tsvetaeva, the opposition of the inner «full» space of genius and external emptiness as necessary conditions for the act of creativity becomes significant. The emptiness surrounding the creator as a potentiality is the main condition for the realization of the gift. It induces to filling, gives the opportunity to express the inner «fullness» of genius.Key words: M. Tsvetaeva, space, opposition, semantic field, creativity.DOI 10.23683/1995-0640-2017-2-187-192